REKSADANA SYARIAH SEBAGAI ALTERNATIF INVESTASI ISLAMI - Rahmawati; Imaduddin, M. Asad; Jufrin (Wahana Islamika Jurnal Studi Keislaman, 2024)
This article aims to find out how Islamic mutual funds can be said to be an Islamic investment alternative. This type of research is library research. The primary data used is the Capital Market Law, Financial Services Authority Regulations and DSN-MUI fatwa. Meanwhile, secondary data used is other literature that is in accordance with the research. The findings in this article are concluded as follows: (1) the mechanism in sharia mutual fund investment starts from the fund owner giving a mandate to the investment manager which is then invested collectively. The investment results will be added to the investor's accumulated funds if there is a profit and will be reduced if there is a loss. Accumulated funds are stored in a custodian bank. After deducting the investment manager's honorarium and other costs, the funds accumulated as Net Active Value (NAB) (2) management of sharia mutual funds has been carried out professionally in accordance with the provisions contained in the DSN-MUI fatwa. Although, there are several conditions that make it possible that sharia principles cannot be implemented optimally.